Proportions of Mycobacterium massiliense and Mycobacterium bolletii Strains among Korean Mycobacterium chelonae-Mycobacterium abscessus Group Isolates - Kim, Hee-Youn (American Society for Microbiology (ASM), 2008)
Korean isolates of the Mycobacterium chelonae-Mycobacterium abscessus group, which had been isolated from two different hospitals in South Korea, were identified by PCR restriction analysis (PRA) and comparative sequence analysis of 16S rRNA genes, rpoB, and hsp65 to evaluate the proportion of four closely related species (M. chelonae, M. abscessus, M. massiliense, and M. bolletii). Of the 144 rapidly growing mycobacterial strains tested, 127 strains (88.2%) belonged to the M. chelonae-M. abscessus group. In this group, M. chelonae, M. abscessus, M. massiliense, and M. bolletii accounted for 0.8% (n = 1), 51.2% (n = 65), 46.5% (n = 59), and 1.6% (n = 2), respectively. Two isolates which showed discordant results, M. massiliense by rpoB sequence analysis and M. abscessus by hsp65 sequence analysis, were finally identified as M. massiliense based on the additional analysis of sodA and the 16S-23S internal transcribed spacer. M. abscessus group I isolates previously identified by hsp65 PRA were all found to be M. abscessus, whereas group II isolates were further identified as M. massiliense or M. bolletii by sequencing of rpoB and hsp65. Smooth, rough, or mixed colonies of both M. abscessus and M. massiliense isolates were observed. M. massiliense strains that were highly resistant to clarithromycin had a point mutation at the adenine at position 2058 (A(2058)) or 2059 (A(2059)) in the peptidyltransferase region of the 23S rRNA gene.